Letter from Max Bredig to Georg Bredig and Marianne and Viktor Homburger, June 24, 1939 - Bredig, Max Albert (1939)
Max Bredig (1902-1977) writes a letter to his family in Germany expressing gratitude for their birthday wishes and providing updates on his life in New York City. He mentions his scientific work, lunch meetings with business friends, and visits to the World’s Fair. However, he also expresses deep concern about the fate of his family and friends in Germany, who are facing increasing antisemitism under the Third Reich. He lastly inquires about his father's immigration paperwork at the American consulate, highlighting the urgency of the matter.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Jews, German; Jewish Holocaust (1939-1945)